Free Will and Determinism: Resolving the Tension - Richard Startup (Open Journal of Philosophy, 2021)
Progress may be made in resolving the tension between free will and determinism by analysis of the necessary conditions of freedom. It is of the essence that these conditions include causal and deterministic regularities. Furthermore, the human expression of free will is informed by understanding some of those regularities, and increments in that understanding have served to enhance freedom. When the possible character of a deterministic system based on physical theory is considered, it is judged that, far from implying the elimination of human freedom, such a theory might simply set parameters for it; indeed knowledge of that system could again prove to be in some respects liberating. On the other hand, it is of the essence that the overarching biological framework is not a deterministic system and it foregrounds the behavioural flexibility of humans in being able to choose within a range of options and react to chance occurrences. Furthermore, an issue for determinism flows from the way in which randomness (e.g. using a true random number generator) and chance events could and do enter human life. Once the implications of that issue are fully understood, other elements fit comfortably together in our understanding of freely undertaken action: the contribution of reasons and causes; the fact that reasons are never sufficient to account for outcomes; the rationale for the attribution of praise and blame.